Rabi'a al-Adawiyya's Devotion to God - Jaoudi, Maria M. (1990)
It took Ibrahim Ibn Adhem fourteen years to reach the Kaaba in pilgrimage, because he said long prayers at every shrine along the way ... but when he got there, there was no Kaaba to be seen. "What is this?" he asked himself. "Have I gone blind?"."No," a Voice said, "you can't see the Kaaba because it has gone out to meet a woman." Burning with jealousy, Ibrahim ran toward the outskirts of Mecca till he ran into Rabi'a, who was just arriving. He turned around, and saw the Kaaba back in its usual place. Then he turned to Rabi'a.
Keywords: Ecological Implications of Sainthood; Purification; Rabia's Teaching Methodology